The sensitivity of method TOPSIS with respect to the normalization rules - Simanavičienė, Rūta (Lietuvos matematikos rinkinys, 2016)
In the most multiple attribute decision making methods the attribute values are provided to transform into one dimension. The normalization of attribute values is not always needed, but it may be essential. This restructuring is carried out in accordance with appropriate normalization rules. It has been observed that some of multiple attribute methods are used for different normalization rules. In practical calculations it noted that using different normalization rules in the same multiple attribute method produces different alternatives priority line, with the same data. Due to the fact of this paper is to carry out normalization methods affect the ranking of alternatives, study. And find out under what conditions the normalization rules change the ranking of alternatives.
Keywords: multiple attribute decision making methods; normalization; statistical analysis; monotonic transformation